PENGARUH EFEKTIVITAS PEMBIAYAAN KUR TERHADAP PENDAPATAN UMKM AGRIBISNIS BANK SYARIAH INDONESIA KC BANDUNG JUANDA - Cahyani, Nova Tri; Setiawan, Iwan (Universitas Galuh, 2023)
The extensive presence of micro, small, and medium enterprises (MSMEs) in Indonesia and their significant contribution to the country's Gross Domestic Product (GDP) underscore the imperative of preserving and nurturing these entities, especially in the context of the Covid-19 pandemic. To address the challenges faced by agribusiness MSMEs in accessing working capital, the government has implemented the People's Business Credit (Kredit Usaha Rakyat or KUR), a low-interest credit scheme. Government-endorsed institutions like BSI KC Bandung Juanda play a pivotal role in supporting these MSMEs. However, an examination of the data concerning the number of agribusiness MSME customers and the associated financing amounts reveals a limited level of interest. This research aims to evaluate the effectiveness of KUR financing on the income of agribusiness MSMEs and explore its influence on their overall revenue. Employing a quantitative methodology, the study employs the Simple Linear Regression approach to analyze the data. The findings of this research demonstrate a significant effectiveness rate of 91.2 percent, indicating the substantial impact of KUR financing on the income generated by agribusiness MSMEs. Furthermore, the study establishes a notable relationship, with KUR financing exhibiting a positive influence of 91.2 percent on the income of agribusiness MSMEs.